Postcolonial India : history, politics, and culture - Damodaran, Vinita; Damodaran, Vinita; Unnithan-Kumar, Maya, 1961- (New Delhi : Manohar, 2000)
Papers, originally presented at an international conference held at Sussex, England in 1997.
Includes bibliographical references (p. [353]-364) and index.